2010
DOI: 10.1071/mf09174
|View full text |Cite
|
Sign up to set email alerts
|

Effects of freshwater flow on the fish assemblage of the Mondego estuary (Portugal): comparison between drought and non-drought years

Abstract: Warming of the planet is indisputable and will lead to more frequent extreme events, such as droughts. From June 2003 to March 2008, the effects of variations in river flow, associated with drought conditions, were studied in the fish assemblage of the Mondego estuary, Portugal. Over this time, two distinct hydrological periods were identified: non-drought years and drought years, with consistent changes in the fish assemblages. In the drought years, salinity increased inside the estuary, displacing the estuar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…Abnormally low mesozooplankton abundances were noted in the NRE during summers of 2008and 2009. Similarly, Reaugh et al (2007 suggesting that lack of food availability (i.e., zooplankton) coupled with seasonal hypoxia affected fish health and population dynamics (Baptista et al 2010;Martino and Houde 2010). In another example, Baptista et al (2010) observed dramatic reductions in the biomass of estuarine resident and nonresident but estuarine-dependent fish species in a European estuary during a severe drought.…”
Section: Multiyear Effects Of Droughts-ecologicalmentioning
confidence: 97%
See 1 more Smart Citation
“…Abnormally low mesozooplankton abundances were noted in the NRE during summers of 2008and 2009. Similarly, Reaugh et al (2007 suggesting that lack of food availability (i.e., zooplankton) coupled with seasonal hypoxia affected fish health and population dynamics (Baptista et al 2010;Martino and Houde 2010). In another example, Baptista et al (2010) observed dramatic reductions in the biomass of estuarine resident and nonresident but estuarine-dependent fish species in a European estuary during a severe drought.…”
Section: Multiyear Effects Of Droughts-ecologicalmentioning
confidence: 97%
“…Similarly, Reaugh et al (2007 suggesting that lack of food availability (i.e., zooplankton) coupled with seasonal hypoxia affected fish health and population dynamics (Baptista et al 2010;Martino and Houde 2010). In another example, Baptista et al (2010) observed dramatic reductions in the biomass of estuarine resident and nonresident but estuarine-dependent fish species in a European estuary during a severe drought. Taken as a whole, the changes in zooplankton biomass and habitat condition, and their subsequent effects on fisheries, suggests that mechanisms by which variable freshwater delivery, including droughts, influence higher trophic levels are complex and require further study (Bennet et al 1995;Livingston et al 1997).…”
Section: Multiyear Effects Of Droughts-ecologicalmentioning
confidence: 99%
“…Several studies from different regions have emphasized abiotic factors, such as temperature and salinity (Harrison & Whitfield, 2006), salinity and turbidity (Cyrus & Blaber, 1992;Barletta et al, 2005), turbidity (Cyrus & Blaber, 1987;Abou-Seedo et al, 1990), morphodynamic models (Inui et al, 2010), and input of freshwater and river flow (Barletta et al, 2005;Vinagre et al, 2009;Baptista et al, 2010;Castillo-Rivera, 2013) as factors that influence the abundance of young fish in these shallow water habitats. Additionally, factors such as recruitment, competition, predation, and structural complexity are listed as ecological processes that determine the structure of these communities, so that the fish assemblages are the result of the complex interaction of abiotic and biotic factors (Mariani, 2001;Laegdsgaard & Johnson, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Costa et al, 2007;Gillson et al, 2009;Martinho et al, 2009), with consequent repercussion on the production levels , as observed by the increased production of Pomatoschistus microps in the years with higher precipitation levels. In general, higher river flow is responsible for an increased transport of organic matter towards estuaries, inducing an increase in primary and secondary production that provides higher food availability for fishes (Costa et al, 2007;Baptista et al, 2010;Dolbeth et al, 2010).…”
Section: Abundance Growth and Productionmentioning
confidence: 99%
“…In particular, fish dynamics, growth and production of estuarine ecosystems seem to be strongly affected by altered hydrology patterns, which can be regulated by floods and drought events (Whitfield, 2005;Dolbeth et al, 2008aDolbeth et al, , 2010Baptista et al, 2010). Fish recruitment, growth and production can also be influenced directly by changes in physico-chemical parameters, such as salinity, turbidity and dissolved oxygen (Pampoulie et al, 2001;Selleslagh and Amara, 2008) or indirectly, through changes in food availability (Whitfield, 2005).…”
Section: Introductionmentioning
confidence: 99%